How do you find the derivative of # y=sqrt(x−3)# using the limit definition?

Answer 1
Given: #f(x) = y = sqrt(x−3)#

Then:

#f(x+h) = sqrt(x+h−3)#

Using the limit definition:

#f'(x) = lim_(h to 0) (f(x+h)-f(x))/h#

Substitute in the functions:

#f'(x) = lim_(h to 0) (sqrt(x+h−3)-sqrt(x−3))/h#
We know that, if we multiply the numerator by #sqrt(x+h−3)+sqrt(x−3)#, we will eliminate the radicals but we must, also, multiply the denominator by the same thing:
#f'(x) = lim_(h to 0) (sqrt(x+h−3)+sqrt(x−3))/(sqrt(x+h−3)+sqrt(x−3))(sqrt(x+h−3)-sqrt(x−3))/h#

Please observe that we have not changed the value of anything, because we have multiplied by 1 in a very special form.

Now, the radicals in the numerator disappear, because of the property #(a+b)(a-b) = a^2-b^2#, and the denominators just multiply:
#f'(x) = lim_(h to 0) ((x+h−3)-(x−3))/(h(sqrt(x+h−3)+sqrt(x−3)))#

Combine like terms in the numerator:

#f'(x) = lim_(h to 0) h/(h(sqrt(x+h−3)+sqrt(x−3)))#

The h in the numerator cancels with the h in the denominator:

#f'(x) = lim_(h to 0) 1/((sqrt(x+h−3)+sqrt(x−3)))#

Now we can allow h to become 0:

#f'(x) = 1/((sqrt(x−3)+sqrt(x−3)))#

Combine like terms:

#f'(x) = 1/(2sqrt(x−3))#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the derivative of ( y = \sqrt{x - 3} ) using the limit definition, we apply the definition of the derivative:

[ f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h} ]

Substitute ( f(x) = \sqrt{x - 3} ) into the definition and simplify the expression:

[ f'(x) = \lim_{h \to 0} \frac{\sqrt{x + h - 3} - \sqrt{x - 3}}{h} ]

To eliminate the square roots in the numerator, we rationalize the expression by multiplying the numerator and denominator by the conjugate of the numerator:

[ f'(x) = \lim_{h \to 0} \frac{\sqrt{x + h - 3} - \sqrt{x - 3}}{h} \cdot \frac{\sqrt{x + h - 3} + \sqrt{x - 3}}{\sqrt{x + h - 3} + \sqrt{x - 3}} ]

[ f'(x) = \lim_{h \to 0} \frac{(x + h - 3) - (x - 3)}{h(\sqrt{x + h - 3} + \sqrt{x - 3})} ]

[ f'(x) = \lim_{h \to 0} \frac{x + h - 3 - x + 3}{h(\sqrt{x + h - 3} + \sqrt{x - 3})} ]

[ f'(x) = \lim_{h \to 0} \frac{h}{h(\sqrt{x + h - 3} + \sqrt{x - 3})} ]

[ f'(x) = \lim_{h \to 0} \frac{1}{\sqrt{x + h - 3} + \sqrt{x - 3}} ]

Now, as ( h ) approaches 0, we evaluate the limit:

[ f'(x) = \frac{1}{2\sqrt{x - 3}} ]

So, the derivative of ( y = \sqrt{x - 3} ) using the limit definition is ( \frac{1}{2\sqrt{x - 3}} ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7